Proteins in Relation to Vigor and Viability of White Lupin (Lupinus albus L.) Seed Stored for 26 Years - Dobiesz, Malwina; Piotrowicz-Cieślak, Agnieszka I. (Frontiers in Plant Science, 2017)
The aim of the study was to evaluate the vigour and viability as well as to determine and compare the contents of selected protein fractions of white lupin seeds stored for 26 years at temperatures of -14oC and +20oC. The seeds stored at -14oC germinated in 86.3 %, while the seeds stored at +20oC did not germinate at all. The viability evaluation was confirmed by the measuring electroconductivity of seed exudates. In seeds stored at -14oC the contents of γ, δ and β conglutin were 14, 4 and 69 mg × g-1, respectively, while in seed stored at +20oC they were 15.5, 3, 65 mg × g-1, respectively. One-dimensional electrophoresis of γ and δ conglutin fractions indicated the presence of several intense polypeptide bands with molecular weights from 23.0 to 10.3 kDa. Polypeptide bands with a molecular weight of 22.4 and 19.8 kDa exhibited almost two times higher expression in the seeds stored at -14oC compared to the seeds stored at +20oC. Electrophoresis revealed 310 protein spots on the maps generated for seeds stored at -14oC, and 228 spots for seeds stored at +20oC. In seeds stored at +20oC most polypeptide subunits had a pH ranging from 4.5 to 7 and a molecular weight of 10-97 kDa. The greatest differences in the contents of polypeptides between the analysed variants was observed within the range of 20-45 kDa (-14oC: 175, +20oC: 115 protein spots) and within the range of 65-97 kDa (-14oC: 103, +20oC: 75 protein spots). In seeds stored at +20oC, a clear decline in basic (8-10 pH) polypeptides was observed. The study demonstrated that the polypeptides identified as γ and δ conglutins are probably closely related to vigour and viability of seeds.